Effects of post-activation potentiation exercises on kicking frequency, fatigue rate and jump performance in taekwondo athletes: a case study (Efectos de los ejercicios de potenciación post activación sobre la frecuencia de pateo, tasa de fatiga y saltabi - Castro-Garrido, Nibaldo; Valderas-Maldonado, Carol; Herrera-Valenzuela, Tomás; Ferreira Da Silva, Jonatas; Guzmán-Muñoz, Eduardo; Vásquez-Gómez, Jaime; Magnani Branco, Braulio; Zapata-Bastias, José; Valdés-Badilla, Pablo; López-Fuenzalida, Antonio (Retos, 2020)
Abstract. The aim of the present study was to establish the effects of three conditions of post-activation potentiation (PAP) exercises on kicking frequency, fatigue rate (FR) and jump performance in novice and advanced taekwondo athletes. Secondarily, to establish if the PAP strength plus plyometrics exercises produced a significantly higher increase with respect to exercises of isolated strength and plyometrics. Eight university taekwondo athletes (n=4 novices and n=4 advanced) were randomized into four (one control and three experimental) intervention conditions. Kicking frequency and FR were evaluated with the Frequency Speed of Kicks Test (FSKT), and countermovement jump test (CMJ). Effect size (ES) was calculated and the significance level was stabilized at p<0.05. Advanced taekwondo athletes obtained significantly higher results when compared to novices in the control condition for the fifth FSKT-10s (p=0.019; ES=2.382); in the strength condition for the second FSKT-10s 2 (p=0.028; ES=2.590); and in the strength plus plyometrics condition for the first FSKT-10s (p=0.037; ES=1.805) and third FSKT-10s (p=0.027; ES=2.117). Furthermore, the control condition showed a difference when compared to strength plus plyometrics: on the first (p=0.040; ES=0.552) and second FSKT-10s (p=0.032; ES=0.687), respectively. The FR and CMJ did not significantly differ between the athletes nor between the intervention conditions. In conclusion, the PAP exercises did not improve kick frequency, FR and jump performance in the taekwondo athletes evaluated. However, these exercises did not produce adverse effects in the FR; thus, they could be used in taekwondo athletes with previous strength training. Resumen. El objetivo del presente estudio fue establecer los efectos de tres condiciones de ejercicios de potenciación post-activación (PAP) sobre la frecuencia de pateo, tasa de fatiga (TF) y saltabilidad en atletas de taekwondo novatos y avanzados. Secundariamente, establecer si los ejercicios de PAP de fuerza más pliometría producen un aumento significativamente mayor respecto a los ejercicios de fuerza y pliometría aislados. Ocho atletas universitarios de taekwondo (n=4 novatos y n=4 avanzados) fueron asignados aleatoriamente a cuatro condiciones de intervención (una control y tres experimentales). La frecuencia de pateo y TF se evaluaron con el Frequency Speed of Kicks Test (FSKT) y la saltabilidad con el salto contramovimiento (CMJ). Se calculó el tamaño del efecto (TE) y se estableció un nivel de significancia de p<0,05. Los atletas de taekwondo avanzados obtuvieron resultados significativamente mayores en comparación con los novatos en la condición control para el quinto FSKT-10 (p= 0,019; TE=2,382); en la condición de fuerza para el segundo FSKT-10s 2 (p=0,028; TE=2,590); y en la condición de fuerza más pliometría para el primer FSKT-10 (p=0,037; TE=1,805) y el tercer FSKT-10 (p=0,027; TE=2,117). Además, la condición control mostró diferencias al compararla con la condición de fuerza más pliometría en el primer (p=0,040; TE=0,552) y segundo FSKT-10s (p=0,032; TE=0,687), respectivamente. La TF y CMJ no presentaron diferencias significativas entre los atletas ni entre las condiciones de intervención. En conclusión, los ejercicios de PAP no mejoran la frecuencia de pateo, TF y saltabilidad en los atletas de taekwondo evaluados. Sin embargo, estos ejercicios no produjeron efectos adversos en la TF, lo que podría favorecer su uso con entrenamiento previo en fuerza.